IMPLEMENTATION OF WORKER REGISTRATION AS PARTICIPANTS OF EMPLOYMENT SOCIAL SECURITY ADMINISTRATORS IN PRIVATE COMPANIES IN PEKANBARU CITY - Sihotang, Tunggul; Afrita, Indra; Harahap, Irawan (EKSEKUSI, 2025)
ABSTRACT Background: Article 15 paragraph (1) of Law Number 24 of 2011 concerning BPJS, regulates the obligation of employers to register themselves and their workers as BPJS Participants." Research objectives: To analyze the implementation of registration; To find inhibiting factors and efforts to overcome them. Research methods: sociological legal research; legislative and case approaches; research location: BPJS Pekanbaru Branch Office; population and samples from relevant sources; data sources: primary, secondary, tertiary; data collection techniques: observation, structured interviews, document/library study; data analysis: qualitative; conclusion: inductive.  Research results: the regulations have not been implemented well. Conclusion: First, the implementation of worker registration as BPJS Employment participants in private companies in Pekanbaru City has not yet been carried out in accordance with legal provisions in 2022 to 2024, where of the 13 companies and cooperatives there are still some workers whose employers have not registered as BPJS Employment participants. Second, the inhibiting factor is the factor of law enforcement/government officials, namely lack of understanding of regulations, efforts to overcome them are providing technical guidance; Lack of supervision and control from local agenciesKeywords: Participants, BPJS, Private Companies ABSTRAK Latar belakang Pasal 15 ayat (1) Undang-Undang Nomor 24 Tahun 2011 tentang BPJS, mengatur kewajiban pemberi kerja mendaftarkan dirinya dan pekerjanya sebagai Peserta BPJS.” Tujuan penelitian: Untuk menganalisis implementasi pendaftaran; Untuk menemukan faktor yang menghambat dan upaya mengatasi. Metode penelitiaan: penelitian hukum sosiologis; pendekatan perundang–undangan dan kasus; lokasi penelitian: Kantor Cabang BPJS Pekanbaru; populasi dan sampel dari narasumber relevan; sumber data: primer, sekunder, tersier; teknik pengumpulan data: observasi, wawancara terstruktur, studi dokumen/kepustakaan; analisis data: kualitatif; kesimpulan:  induktif.  Hasil penelitian: regulasi itu belum diimplementasikan dengan baik. Kesimpulan: Pertama, Implementasi pendaftaran pekerja sebagai peserta BPJS Ketenagakerjaan pada perusahaan swasta di Kota Pekanbaru belum berjalan sesuai ketentuan hukum di tahun 2022 sampai 2024, dimana dari 13 perusahan dan koperasi masih ada sebagian pekerja yang belum didaftarkan pemberi kerjanya sebagai peserta BPJS Ketenagakerjaan. Kedua, Faktor yang menghambat ialah  Faktor aparat penegak hukum/pemerintah yaitu kurang memahami regulasi, upaya mengatasinya menyelenggarakan bimbingan teknis; Kurangnya pengawasan dan kontrol dari dinas setempatKata Kunci: Peserta, BPJS, Perusahaan Swasta